Sleep problems in preschool children at the child development center with different developmental status: A questionnaire survey - Kuok, Chi-Man; Liu, Jia-Rou; Liang, Jao-Shwann; Chang, Shao-Han; Yang, Ming-Tao (Frontiers in Pediatrics, 2022)
Objective: To investigate the relationship between sleep problems and development in preschool children with suspected developmental delay. Methods: A total of 192 preschool children (mean age 4 years; 131 males, 61 females) were recruited from the Child Development Clinic, including 98 preterm children and 94 age- and sex-matched full-term children. All participants underwent evaluation of gross motor, fine motor and speech performance. All parents of all participants completed the Children’s Sleep Habits Questionnaire (CSHQ). Some of the participants also underwent psychological evaluation. Correlation analysis and community network analysis were used to investigate the interactions. Results: The developmental status was: 75.5% developmental delay, 19.3% borderline development, and 5.2% normal development. Eighty-nine percent of the subjects had abnormal CSHQ scores. Age, gestational age, speech development, cognitive development, and socio-emotional development were significantly correlated with the CSHQ. Significant interactions between sleep problems and development were noted mostly in the preterm group. Conclusion: High prevalence of sleep disturbances in children at the Child Development Center was noted and associated with multiple factors. Therefore, during the multidisciplinary evaluation of children with possible developmental delay, inquiring about their sleep quality and habits is strongly recommended. Mitigating sleep problems enhances the efficacy of early intervention programs.